(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In recent years, the increasing attention of scientific and expert public are attracted cases of stalking. Amendments to the Criminal Code which came into effect on 01 June 2017 (Republic Serbia, Official Gazette“ No 94/16) for the first time includes the criminal act of stalking in Republic of Serbia legislation, in its Article 138a. Stalking has been included in Chapter XIV, within the group of criminal acts againts citizens rights and freedoms. With this act, Republic of Serbia has joined the family od those European countries which apply Article 34 of the Convention on Preventing and Combating Violence against Women and Domestic Violence, to incriminate such deliberate behaviour, where repeated threats made to another person cause that person′s fear for their safety. The authors in the paper will give analysis of the legal text from two aspects: legal – criminal and crminological. In the next part of this article, the authors will analyse bearing stalking and family violence in terms of the Code on the prevention of domestic violence. Finaly, the authors discuss the inadeqacy of this legislation and the need for further legislative intervention in this area